A Correlation of Duration of Diabetes with Glycemic Indices in the Type 2 Diabetes Mellitus: A Prospective Study - Kumar Gupta, Anil (Asian Journal of Medical Research, 2019)
Background: The development of chronic complications is related to the duration of Diabetes Mellitus, however it may not reflect the true duration of disease, rather it reflects the time since diagnosis. The aim of this study to correlation of glycemic indices with duration of diabetes. Subjects and Methods: An observational study has done on 100 patients with type 2 diabetes mellitus in department of medicine, MSY Medical College & Hospital, Lalpur, Meerut. Diabetes was diagnosed according to American Diabetes Association (ADA) revised criteria. Blood glucose level estimation was done by glucose oxidase method in venous blood. Glycosylated haemoglobin (HbA1C) was measured by ion-exchange chromatography method. Results: Our results showed that the 5-10 years of duration of diabetes was present in 42% cases and less than 5 years duration of diabetes was present in 40%. HbA1c was not significant correlate but >10 years duration of diabetes was higher mean value as compared to less than 5 year duration of diabetes. Conclusion: We concluded that on applying spearman correlation for microvascular complications, a positive association was observed for age of patients, duration of diabetes, HbA1C. Duration of diabetes was found to be a main culprit of micro vascular complication.